When bias is implicit, how might we think about repairing harm?. (December 2015) - Banaji, Mahzarin R; Bhaskar, R; Brownstein, Michael
Highlights: Shows that implicit bias can lead to disparate impact on protected social groups. Considers the nature of moral responsibility in institutional contexts. Notes three possible options for repairing the harms done by unintended forms of bias. Abstract : A recent Supreme Court decision — Texas Department of Housing and Community Affairs v. Inclusive Communities Project, Inc. — creates an opening to consider models for repairing the effects of unintended harm. We mention some results from the science of unconscious bias, consider the nature of n-to-n harm, cite recent philosophical arguments about responsibility for carrying implicit bias, and note the legal status of intent versus impact in civil rights law. Based on the opportunity presented by Inclusive Communities, we present three options for repairing unintended harm, placing emphasis on litigation-minimizing solutions, especially insurance.